(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2024)
Quantum Dot (QD) Solar Cells have emerged as promising candidates for next-generation photovoltaic technologies due to their tunable bandgaps, solution processability, and potential for low-cost fabrication. However, their photovoltaic performance is often limited by factors such as low light absorption and charge carrier recombination. Plasmonic nanostructures, which exploit the resonant oscillation of conduction electrons in metallic nanoparticles, offer a viable strategy to enhance light absorption and improve charge carrier dynamics in QD solar cells. This paper reviews the integration of plasmonic nanostructures with QD solar cells, examining the mechanisms by which plasmonics can enhance photovoltaic performance. We discuss various types of plasmonic materials, their configurations within solar cell architectures, and the resultant improvements in efficiency. Additionally, the challenges and future prospects of plasmonic-enhanced QD solar cells are explored.